Removal of phosphate from wastewater using coal slag. Issue 15 (8th December 2021) - Hoang Lam, Nguyen; Ma, Hoa Thai; Bashir, Mohammed J. K.; Eppe, G.; Avti, Pramod; Nguyen, Tan Tai
ABSTRACT: Adsorption is an efficient, cost-effective, and eco-friendly method for the treatment of phosphorus from wastewater. This work presents the adsorptive removal of phosphate ions in aqueous solution using coal slag (CS) from a thermal power plan. The surface morphological analysis showed that the CS particles were around 50 µm with a surface area of 9.20 m 2 g −1 and adsorption average pore width of 6.42 nm, offering the high capability for phosphate ions adsorption. The optimising phosphate ions adsorption conditions were investigated based on various parameters, including contact time, pH, and amount of absorbent. The experimental results showed that the maximum loading adsorption capacity was 21.63 mg g −1 in the concentration range of 0–30 mg L −1 under optimising conditions (i.e. pH of 6, adsorbent dosage (0.1 g vol −1 used) and contact time of 45 min). Furthermore, the use of CS offers several benefits like reducing the sample pre-treatment steps for costly, less time-consuming and reliable methods.